Malory's contemporary audience the social reading of romance in late medieval England - Crofts, Thomas 1968- (Boydell & Brewer, 2006)
This book seeks to place Malory's 'Morte Darthur' more firmly in its cultural and historical context. Its composition, in the mid to late fifteenth century, took place at a time of great upheaval for England, a period beginning with the loss of Bordeaux [and the Hundred Years War] and ending with the rise of Richard III. During this time the 'Morte' was translated from numerous French sources, copied by scribes, and, finally, in July 1485, printed by William Caxton. The author argues that in this unique production history are reflected the ideological crises which loomed so massively over England's ruling class in the fifteenth century; and that the book is in fact inseparable from these crises. THOMAS H. CROFTS is Assistant Professor of English at East Tennessee State University